Effectiveness of Local Government Supervision in Small Business Licensing: An Empirical Study of The Ampyang Industry in Gadingan Village in Mojolaban - Amanda Maulida Rohmah; Arief Budiono; Suni Tuti (Universitas Muhammadiyah Surakarta, 2026)
The growth of local food-based small businesses, particularly the ampyang industry in Gadingan Village, has demonstrated significant economic contributions, but still faces issues of business legality and weak licensing oversight by the local government. This study offers novelty by specifically analyzing the effectiveness of local government oversight in licensing small businesses at the village level and its implications for legal protection and business development, which have not been widely studied. This study aims to analyze the effectiveness of local government oversight of the legality and development of small businesses in the ampyang industry and examine the views of business actors on the implementation of such oversight. The method used is empirical juridical with a legislative and sociological approach through in-depth interviews and literature studies. The results of the study indicate that supervision has been carried out through data collection, legality checks, licensing socialization, and coaching, which has resulted in increased legal awareness for business actors. However, its implementation has not been optimal due to limited resources, lack of coordination, and uneven oversight coverage. Business actors assess supervision as positive because it not only functions as administrative control but also provides mentoring, increases market confidence, and supports business development. Therefore, the effectiveness of local government supervision plays a crucial role in promoting the sustainability of small businesses based on the local economy.